VLE and activity coefficients of ionic liquids + water systems - Saraiva, Catarina Ribeiro (2018)
The industrial progress is a phenomenon more and more present worldwide, where it is possible to observe an increasing demand for innovation, which therefore results in competitiveness and growth. A consequence of this innovation is the discovery of a novel type of compounds such as: the ionic liquids. These have attracted a high interest in the recent years due to its characteristics, namely: low vapour pressure, good thermal stability, etc. This new class of compounds has a large range of applications, for instance in cooling absorption. The industrial application of ionic liquids (ILs) requires the knowledge of their termophysical properties, their phase behaviour and of their mixtures. This work addresses the study of those thermodynamic properties of water + ionic liquids systems using the state equation soft-SAFT EoS, the ILs under study are: 1-butyl-3-methyli midazolium trifluoromethanesulfunate, 1-butyl-3-methylimidazolium tosylate, 1-butyl-3-methylimidazolium trifluoroacetate, 1-butyl-3-ethylimidazolium methanesulfunate, 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium thiocyanate. This work also addresses the description of water activities in ionic liquids. The study began by starting to define the appropriate association scheme of each ionic liquid, then molecular parameters for each compound were regressed using density data at atmospheric pressure, always trying to find the parameter set with the lowest error in the density description. Then it was initiated the vapour-liquid equilibria study of binary systems composed by water + ionic liquid, this study was made for seven mixtures, composed by the ILs previous mentioned and for three different pressure values, namely : 0.1 MPa, 0.07 MPa and 0.05 MPa. Finally, it was started the water activities coefficients study, of the seven systems in order to select the best pair water + IL that best satisfies the application referred above.